ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN KIMIA KELAS X DI SMA NEGERI 1 SUNGAI AMBAWANG - Yakina Yakina; Tuti Kurniati; Raudhatul Fadhilah (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThis study aimed at discovering the students’ in chemistry class at grade X of SMA Negeri 1Sungai Ambawang. A qualitative descriptive method was employed in this study. As many as62 students participated as the subjects. Two techniques were used in this study. They weremeasurement and indirect communication techniques. The indirect technique used 30 testquestions and 30 items of questionnaire. The result of analysis indicated that the students who had problems in understanding the terms were 48,99 %, the students who had problem in understanding the concept were 41,32%, and the students who had problems in calculating were 70,97%. The results of the questionnaire showed that the internal factors of motivation and interest were 59,25%. This is considered as the influential factor in the students’ difficulties. While the external factor, with the average percentage of 85,4% deal with the students’ difficulties were family, facilities and infrastructures, family condition, school, teachers, learning facilities, school building, mass media, and neighborhood. This is considered as the factor that didn’t influent the students’,difficulties in chemistry class.Keywords: Analysis, learning difficulties, chemistry learning